Making moral sense : beyond Habermas and Gauthier - Gunnarsson, Logi (Cambridge studies in philosophy., 2000)
"Logi Gunnarsson takes issue with the assumption made by many philosophers faced with the problem of reconciling moral norms with a scientific world view, namely that morality must be offered a non-moral justification based on a formal concept of rationality. He argues that the criteria for the rationality of an action are irreducibly substantive, rather than purely formal, and that assuming that morality must be given a non-moral justification amounts to a distortion of both rationality and morality. His discussion includes substantial critical engagement with major thinkers from two very different philosophical traditions, and is notable for its clear and succinct account of Habermas' discourse ethics. It will appeal to anyone interested in practical reason and the rational credentials of morality."--Jacket